Global health-based virtual exchange to improve intercultural competency in students: Long-lasting impacts and areas for improvement - Case, Stuart J.; Collins, Sarah L.; Wood, Elizabeth A. (Frontiers in Public Health, 2022)
Introduction As public health expands its role in global settings, the need to develop intercultural competency for public health students also grows. One initiative being applied to promote global awareness is the use of virtual exchange (VE) programs. VE programs promote collaborative online international learning (COIL) and allow students from different countries to connect and work together on projects related to their field of study; however, there is little research around the long-term impacts of these programs. Methods Undergraduate pre-health students from the United States who participated in a VE program a year prior were interviewed about their experiences engaging with undergraduate medical students in Egypt. They were asked if the experience impacted their current behaviors, skills, or knowledge, and what improvements could be made to the program. Mezirow's Transformative Learning Theory (TLT) served as the theoretical framework, grounding interview instrument development and directed content analysis procedures. Researchers also engaged in inductive analysis to capture other salient themes. Results Ten students were interviewed with a majority engaging in either of the two final stages of Mezirow's TLT: “building of self-confidence and self-competence” (60%) and “reintegration” (50%). Other salient themes found were intercultural interactions, VE appreciation, and VE improvements. When describing their experience in one word, students overwhelmingly provided words with positive connotations (80%), with the negative responses being explained by the structure and presentation of the VE. Discussion Students were able to apply lessons they learned during the VE within a 1-year follow-up period. This is beneficial, as health professionals require intercultural competency to promote and provide improved health outcomes. Results from this study indicate the need for structure when conducting a VE, addressing the need to increase the number of direct interactions and thereby promoting more intercultural exchanges. Likewise, the interviews demonstrated that changes in course instruction need to be implemented gradually to allow for students to adjust to unfamiliar teaching methods.